Composition of Pancarli Magmatic Ni-Cu±(PGE) Sulfide Deposit in the Cadomian-Avalonian Belt, Eastern Turkey - Yildirim, Esra; Yildirim, Nail; Donmez, Cahit; Gunay, Kurtulus; Korkmaz, Taner; Akyildiz, Mustafa; Goren, Burcu (China Univ Geosciences, Wuhan, 2020)
Pancarli Ni-Cu +/-(PGE) sulfide deposit occurs in the Neoproterozoic basement complex of the Bitlis massif, which is one of the Andean-type active continental margin fragments with arc-type assemblages represented by the Cadomian orogenic belt. Pancarli sulfides are associated with quartzo-feldspathic gneisses (country rock) and mafic intrusions (host rock). Composed of only semi-massive ore, the Ni-Cu +/-(PGE) sulfide deposit is a small-scale deposit, and it does not contain net-textured and disseminated ore. The mineral assemblage comprises pyrrhotite, pentlandite, and chalcopyrite. The semi-massive ore samples contain 2.2 wt.%-2.9 wt.% Ni, 0.8 wt.%-2.2 wt.% Cu (Cu/(Cu+Ni)=0.2-0.5) and 0.13 wt.%-0.17 wt.% Co. The Cu/Ni ratios (average 0.57) are consistent with the segregation of sulfides from a basaltic magma. Low Pt+Pd(100%S)values of 0.08 ppm-0.89 ppm, relatively low Pt/Pd ratios of 0.2-1.4, and Pd/Ir ratios of 4.5-39 have also been revealed. These values demonstrate that the magma reached S saturation before its emplacement and the mineralization with high Cu/Pd ratios formed by sulfides segregated from a PGE-depleted magma. delta S-34 isotope values (average -3.1 parts per thousand) of Pancarli sulfides are lower than mantle source. Negative delta S-34 value indicates contamination from surrounding rocks. Concerning the composition, remobilization style and magma type, the Pancarli Ni-Cu +/-(PGE) sulfide deposit is similar to the deposits associated with Andean-type magmatic arcs located in the convergent plate margin settings.
Keywords: Ni-Cu +/-(PGE) sulfide deposit; delta S-34 isotopes; Neoproterozoic; Andean type; eastern Turkey